3D hierarchical rose-like Ni2P@rGO assembled from interconnected nanoflakes as anode for lithium ion batteries. Issue 7 (23rd January 2020) - Cai, Gan; Wu, Zhenguo; Luo, Tao; Zhong, Yanjun; Guo, Xiaodong; Zhang, Zhiye; Wang, Xinlong; Zhong, Benhe
Abstract : In recent years, anode materials of transition metal phosphates (TMPs) for lithium ion batteries have drawn a vast amount of attention, due to their high theoretical capacity and comparatively low intercalation potentials vs. Li/Li + . Abstract : In recent years, anode materials of transition metal phosphates (TMPs) for lithium ion batteries (LIBs) have drawn a vast amount of attention from researchers, due to their high theoretical capacity and comparatively low intercalation potentials vs. Li/Li + . However, in practice, their application remains constrained by poor electrical conductivity, and dramatic volume expansion and severe agglomeration during the lithium process, which leads to questionable kinetic issues and a prompt decline in capacity during cycling. Herein, through an elaborate design, we developed a novel three-dimensional (3D) hierarchical rose-like architecture self-assembled from two-dimensional (2D) Ni2 P nanoflakes immobilized on reduced graphene oxide (rGO) via a combination of a hydrothermal process and phosphating treatment. Such a design provides unique superiority for Ni2 P-based anode materials for LIBs. Paraphrasing, the 3D hierarchical structure of Ni2 P distributes the stress on the anode material while cycling and provides more lithium storage space. The rGO not only enhances the conductivity of materials, but also serves as a flexible framework which immobilizes Ni2 P so that it prevents it from pulverization. Therefore, the synergistic effect between them guarantees the integrity of the material structure after a long-term cycling Li + intercalation and deintercalation process. When it acted as anode material for LIBs, the as-obtained 3D rose-like Ni2 P@rGO electrode exhibited a noticeable electrochemical performance, which delivers a discharge capacity of 330.5 mA h g −1 at a current density of 100 mA g −1 after 100 cycles and retains 200.5 mA h g −1 at 1000 mA g −1 .